Imperatives of regional economic integration in Asia in the context of developmental asymmetries: Some policy suggestions - Ram Upendra Das (Asian Development Bank Institute (ADBI), 2009)
Regional economic integration agreements are considered to be important policy mechanisms to address regional developmental asymmetries. The Asian reality is characterized by developmental asymmetries across countries on the one hand and a lack of comprehensive pan-Asian formal regional economic integration agreements on the other. The need for such regional agreements is of paramount importance given the phenomenal economic performance of Asia. Against this backdrop this paper tries to describe the nature and extent of developmental and growth asymmetries in Asia. Some conceptual aspects of growth asymmetries are summarized before undertaking an econometric exploration of growth convergence in the Asian region in comparison to some other prominent regions of the world. The paper finds some evidence of growth divergence among East Asia Summit (EAS) countries though it is statistically not significant. This divergence, combined with a strong logic for evelopingdeveloping and developed-developing inter-country cooperation in the EAS region help the paper to make some policy suggestions, especially regarding enabling the less developed countries of EAS to achieve global market access in order to assist development and growth convergence in the region.
Keywords: F15; O19; O47; 330